B-mode and power Doppler sonographic findings in the long bicipital tendon in ankylosing spondylitis - Ozgocmen, Salih; Kiris, Adem; Kaya, Arzu (My University, 2005)
Objectives: The aim of this study was to assess B-mode and power Doppler ultrasound findings of long head of biceps tendon in patients with ankylosing spondylitis (AS). Methods: Anthropometric measurements were carried out and disease activity and functional status were evaluated with BASDAI, BASFI, Dougados Functional Index (DFI) and Articular Index (DAI) in 30 patients with AS. The Shoulder Disability Questionnaire (SDQ) was performed. Pressure pain threshold (PPT) was measured on bilateral long head of biceps tendon and B-mode and power Doppler ultrasound were carried out. Focal changes (hypoechogenic areas within the tendon), calcification of the tendon, and fluid collection inside or outside the tendon sheath at bicipital groove (peritendinous hypoechoic rim) and vascularity of the peritendinous region were assessed. A cumulative ultrasound score (CUSS) was obtained. Results: Focal changes were present in five tendons of four patients. Calcification of the tendon was present in three tendons of three patients. Biceps tendon sheath effusion (peritendinous hypoechoic rim) was observed in 10 tendons of eight patients. Thirteen tendons of eight patients had discernible flow signals, six were inside the tendon sheath (within the hypoechoic rim) and seven were outside the tendon sheath. Cumulative US score correlated significantly with DFI and ESR. There was not a significant correlation between CUSS and total PPT. Conclusion: Ultrasound examination of the long head of biceps tendon gives detailed information of the tendon and PDUS has the potential to be able to show inflammatory activity of the tendon. ©Asia Pacific League of Associations for Rheumatology.
Keywords: Ankylosing spondylitis; Biceps tendon; Power Doppler ultrasound; Shoulder